Analysis of the spatial distribution of germanium in the coal seam c8H of Dniprovska mine field (Ukraine) - Ishkov, Valerii; Kozii, Yevhen; Chernobuk, Oleksandr; Pashchenko, Pavlo; Lozovyi, Andrii (International Science Group, 2022)
The actuality of research of the studying the germanium content in coal seams is due to the possibility of its industrial extraction and use as a valuable accompanying component. The purpose of the work: to establish a relationship between the germanium content and the thickness and ash content of the coal seam с8н of the "Dniprovska" mine field.
Keywords: germanium; "Dniprovska" mine; concentration; spatial distribution